1992
DOI: 10.1007/bf00051152
|View full text |Cite
|
Sign up to set email alerts
|

Hibernating myocardium in patients with coronary artery disease: Identification and clinical importance

Abstract: The term hibernating myocardium describes a particular outcome of myocardial ischemia in which myocytes show a chronically depressed contractile ability but remain viable. Revascularization of hibernating tissue causes a recovery of mechanical function that correlates with long-term survival. Therefore it is important clinically to distinguish hibernating from infarcted myocardium, since asynergies due to hibernation will improve on reperfusion, whilst those due to infarct will not. One suggested technique to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…This may possibly have led to a higher interanimal variation that, when coupled with our small sample size, may have prevented us from achieving statistically significant measurements that might be obtainable with a larger sample size or less interanimal variation. At the dosage level of dobutamine used (10 pg/kg/min), echocardiographic studies have shown that areas with diminished blood supply due to moderate stenoses will be dyskinetic or hypokinetic; whereas at lower dobutamine levels ( e g , 2.5 pglkglmin), contraction is maintained in these areas (42)(43)(44). Our findings in the ANT region at the StD state are consistent with these echocardiographic studies.…”
Section: Quantitative Strain and Deformation Parameterssupporting
confidence: 93%
“…This may possibly have led to a higher interanimal variation that, when coupled with our small sample size, may have prevented us from achieving statistically significant measurements that might be obtainable with a larger sample size or less interanimal variation. At the dosage level of dobutamine used (10 pg/kg/min), echocardiographic studies have shown that areas with diminished blood supply due to moderate stenoses will be dyskinetic or hypokinetic; whereas at lower dobutamine levels ( e g , 2.5 pglkglmin), contraction is maintained in these areas (42)(43)(44). Our findings in the ANT region at the StD state are consistent with these echocardiographic studies.…”
Section: Quantitative Strain and Deformation Parameterssupporting
confidence: 93%
“…The most useful investigations are echocardiography at rest and with dobutamine stress, and nuclear cardiology using either single photon (SPET) or positron emitting (PET) tracers of myocardial viability and perfusion. Contrast echocardiography, ultrasonic tissue characterization, gated SPET and PET and magnetic resonance imaging and spectroscopy have also shown their potential but they are less widely used [13,14] In general terms, the functional techniques (stress echocardiography and magnetic resonance imaging) are specific but insensitive for the prediction of segmental functional recovery, and the radionuclide tracer techniques are sensitive but non-specific [15,16] . It is possible that the lower specificity of the tracer techniques is not a drawback since they have been shown to predict improvement in symptoms and outcome and, as explained above, recovery of segmental function may not be the only important factor.…”
Section: See Page 1358 For the Article To Which This Editorial Refersmentioning
confidence: 99%
“…Acute coronary failure with foci of degeneration is a focal ischemic myocardial injury without necrosis; it can be reversible ("hibernated myocardium") [2,8,9]. Coronary bloodflow deficit in hibernated myocardium is insufficient for necrosis development, but it can cause pH changes, which, in turn, impairs contractile function of cardiomyocytes [7]. Clinically this form of coronary disease differs little from small focal myocardial infarction.…”
mentioning
confidence: 98%